Automated communications in structural organisation of information law - Perepelitsa, Elena V. (Journal of the Belarusian State University. Law, 2025)
The article is devoted to a new direction of information and legal research related to automated communications. The author draws attention to the static nature of legal approaches which help sometimes to assess the processes of networking and platformisation. The carried out analysis is a step along the way of development of a theory that gives a systematically organised idea of information (networked, seamless, computer-mediated) interaction in terms of its legal nomination, correlation with various elements of the information law structure. The author raises the question about the problems solved using automated interaction, including communication between government and public institutions, coordination of public and private interests. New approaches to structuring of law, the use of which creates prerequisites for stabilisation of its condition in the rapidly changing information reality are shown.